Oxytocin Reduces the Attractiveness of Silver-Tongued Men for Women During Mid-Cycle - Gao, Zhao; Ma, Xiaole; Zhou, Xinqi; Xin, Fei; Gao, Shan; Kou, Juan; Becker, Benjamin; Kendrick, Keith M. (Frontiers in Neuroscience, 2022)
In humans, the neuropeptide oxytocin promotes both attraction towards and bonds with romantic partners, although no studies have investigated whether this extends to the perceived attractiveness of flirtatious language. In a within-subject, randomized double-blind placebo-controlled behavior and functional magnetic resonance imaging (fMRI) paradigm (https://clinicaltrials.gov/show/ NCT03144115), seventy-five women rated the attractiveness of either a male face alone or paired with a verbal compliment which varied in terms of topic (women or landscapes) and figurativeness (novel or conventional metaphors or literal expressions). Subjects were tested in fertile and luteal phases of their cycle and on both occasions received either 24IU intranasal oxytocin or placebo. Results showed that, whereas under placebo women in the fertile phase rated the facial attractiveness of men producing novel metaphorical compliments higher than in their luteal phase, following oxytocin treatment they did not. Correspondingly, under oxytocin the faces of individuals producing novel metaphorical compliments evoked greater responses in brain regions involved in processing language (middle frontal gyrus) and cognitive and emotional conflict (posterior middle cingulate and dorsal anterior cingulate) but reduced functional connectivity between the dorsal anterior cingulate and right orbitofrontal and medial frontal gyri. Thus, sex hormones and oxytocin may have opposite effects in regulating mate selection in women during their fertile phase. Novel metaphorical compliments convey a greater sexual than bonding intention and thus while sex hormones at mid-cycle may promote attraction to individuals communicating sexual rather than bonding intent, oxytocin may bias attraction away from such individuals through increasing cognitive and emotional conflict responses towards them.